Journeys in crystal energy landscapes: actual and virtual structures in polymorphic 5-nitrobenzo[c][1, 2, 5]thiadiazole. Issue 5 (16th January 2023) - Gentile, Francesco Silvio; Parisi, Emmanuele; Centore, Roberto
Abstract : Few crystal structures are observed, out of the many possible ones, because of strong selection playing at the level of prenucleation clusters. Abstract : A new polymorph of 5-nitrobenzo[ c ][1, 2, 5]thiadiazole, polymorph II, has been discovered. This polymorph is obtained by crystallization from solutions containing Cu(ii ) ions, which inhibit the formation of the already known polymorph I. The packings of the two polymorphs (actual crystal structures) are compared between each other and also with seven virtual polymorphs generated from the crystal structures of similar compounds retrieved from the CSD and optimized by ab initio calculations with periodic boundary conditions. The comparison is based on the analysis of the synthons present in the different crystal structures, and on calculated lattice energy and density. For the specific case examined, our analysis suggests that among crystal structures containing a given synthon, or a given combination of synthons, only the one with the lowest U lat is observed; crystal structures with slightly higher U lat (within 2 kcal mol −1 ) can be observed, but they must be based on different synthons.